Exploring Idioms in the Movie Script of “Moana” by Ron Clements and John Musker - Sugiarto, Andini; Situngkir, Flora; Manullang, Novry G; Madina (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2023)
An idiom is a word or phrase whose meaning is not always evident from its literal definition but is implicitly understood by native speakers of a particular culture. This study aims to investigate English Idioms in the movie script “Moana” By Ron Clements and John Musker using a large corpus. Examining usage statistics can provide a general understanding of English idiomatic terms. This study seeks to provide a description of idioms that takes into account Fernando and Heasley’s theory. Based on the research, it can be seen that there are 16 idioms in total from the movie Moana. Fernando’s theory separates these into seven pure, six half-pure, and three literal idioms. On the other hand, Heasley’s theory helps to undergo each of the meanings.